Measuring Public Perception of Service Quality and Government Policy in Batubara District, a Survey Analysis - Masitho, Beby; Siregar, Nina Siti Salmaniah; Hidayat, Nasrullah; Angelia, Nina; Riadi, Selamat (Universitas Padjadjaran, 2024)
This research aims tois to analyze public satisfaction community through with seven regional work organizations (OPD). Types of this research is quantitative descriptive with a questionnaire instrument. The number of respondents was 270 respondents and the key informant was 7 respondents. The data processing technique applied questionnaires and interviews; while data analysis used qualitative analysis. The average achievement of the Public Satisfaction Index on the 7 OPDs selected in the Batu Bara district in 2023 was 80,446 with the category GOOD. This was characterized by the provision of public goods and services to meet the community's requirements for public services. The Public Satisfaction Index of 7 (seven) Regional Work Organizations (OPDs) of the highest public service component was the Service Procedure, which is 3,329.